Fear in Bureaucracy: Comparing Public and Private Sector Workers' Expectations of Punishment. Issue 2 (February 2020) - Jung, Jiwon; Bozeman, Barry; Gaughan, Monica
When employees fear punishment for taking initiative, organizations are likely to be less effective and, equally important, such fear extracts a human toll, often contributing to a variety of manifestations of unhappiness including diminished health. We focus on two different types of fears of punishment, fear of being punished for presenting new ideas and for bending organizational rules. Employing Mechanical Turk crowdsourcing data from 1, 189 participants in the 2015 survey of National Administrative Studies Project Citizen, we test hypotheses about possible differences in fear of punishment according to sector (government vs. business), general risk propensity, views about coworkers, job clarity, gender, and whether respondents are members of an underrepresented racial or ethnic minority. Using nested robust regression models, we find that the two different types of fear of punishment are predicted by different variables. Sector has no bearing on fear of punishment for presenting new ideas but is a major predictor of differences in fear of bending the rules, with government employees being more fearful. While gender has no significant effects, being a racial minority is closely related to fear of presenting new ideas. Having a negative view of one's fellow workers, particularly one's supervisor, is associated with greater fear of punishment from both rule bending and presenting new ideas. Those with a clear organization mission and job clarity are less likely to be afraid of punishment for proposing innovative ideas but not necessarily for bending rules. We suggest that the results have implications for managerial practice and human resource reform.